THE IMPACT OF COLLABORATIVE LEARNING ON STUDENTS' HISTORICAL UNDERSTANDING IN SOCIAL STUDIES - Musnar Indra Daulay; Iqbal Erwanda (Penelitian dan Pengembangan Ilmu, 2025)
Traditional history instruction often faces challenges in deeply engaging students, tending to focus on memorizing facts rather than developing conceptual and interpretive understanding. To address this, innovative approaches such as Collaborative Learning (CL) are crucial. This semi-systematic narrative review explores empirical evidence regarding the impact of CL on students' historical understanding in Social Studies, comparing it with traditional teaching methods. The literature indicates that CL significantly improves students' factual, conceptual, and interpretive understanding through social interactions, discussions, and project-based activities. CL has also been shown to strengthen critical and analytical thinking skills, enabling students to analyze historical events from multiple perspectives. The effectiveness of CL is moderated by factors such as student motivation, critical thinking skills, group dynamics, and teacher facilitation. While CL demonstrates positive outcomes, this review identifies significant research gaps, including a lack of longitudinal studies, a limited focus on interpretive understanding, a lack of concurrent quantitative and qualitative comparative studies, and the need for contextualization in developing countries. This review contributes to collaborative learning theory and Social Studies pedagogy by outlining the mechanisms by which CL influences historical understanding and providing practical implications for educators and curriculum developers.